How did you Help the Student to Solve the Problem? Analysis of the Strategies Used by Academic Writing Tutors - Andueza-Correa, Alejandra (2023)
Objective. This research aims to study peer tutoring focused on academic writing to categorize and describe the strategies that a group of tutors from a private Latin American university employs to support students’ academic literacy development. Method. We conducted a qualitative diary study, in which we analyzed 203 diary entries from 13 tutors, following the constant comparative analysis method proposed by grounded theory. Results. Eleven categories emerged from data that can be grouped into two major categories: collaborative writing strategies and strategies for the development of metacognition in writing. Conclusions. We described and categorized diverse tutorial strategies that can be explicitly taught during tutor training programs to promote the development of academic writing skills in less advanced students.